Backtesting VaR for Hong Kong Financial Stocks - Lui, Chun Yin (2022)
The focus of this paper is to examine the effectiveness of VaR. Thus, 11 financial stocks in Hong Kong have been chosen to be the research subject because Hong Kong is one of the world's most important stock trading centres, and the financial sector plays a vital role in Hong Kong's economy. Therefore, the research question is to examine which VaR model, which are historical simulation, historical simulation with volatility adjustment and the parametric approaches, are the most reliable in estimating the potential loss of Hong Kong financial stocks. After conducting backtesting, it is found that the parametric approach is the most reliable VaR model among these three models because the exceedances estimated by this model are mostly consistent with the assumption.